Instructional Leadership Behavior of Elementary School Principals in Bandar Lampung City - Ujang Efendi; Bujang Rahman; Sowiyah Sowiyah; Atik Rusdiani; Diah Ayu Sucitra; Marsasanda Andarin; Sapta Isniar Rahman (Edumaspul: Jurnal Pendidikan, 2025)
This study aims to describe the instructional leadership behavior of elementary school principals in Bandar Lampung. The research method used is descriptive qualitative with data collection techniques through interviews, observation, and documentation. The research informants consisted of one principal and six classroom teachers at SD Negeri 04 Bumiwaras Bandar Lampung. The results of the study show that the principal has implemented instructional leadership through three main dimensions, namely defining the school's mission, managing instructional programs, and building a positive learning climate. The principal plays an active role in formulating the vision and mission, supervising and evaluating learning, coordinating the curriculum, and monitoring student development. In addition, the principal also strives to maintain time discipline, provide rewards, and support teachers' professional development. However, this study also found several obstacles, particularly in terms of communication and delays in conveying information, which can reduce the effectiveness of program implementation. These findings confirm that instructional leadership is a key factor in improving the quality of education, so optimization of coordination and communication is needed in order to achieve maximum results.